Occurrence of acute lower limb injuries in artistic gymnasts in relation to event and exercise phase - Kirialanis, P.; Malliou, P.; Beneka, A.; Giannakopoulos, K. (British Journal of Sports Medicine, 2003)
Objectives: To record the incidence of lower limb injuries (acute and overuse syndromes) in Greek artistic gymnasts in relation to the event and exercise phase. Methods: A total of 162 gymnasts (83 male and 79 female athletes) participating in the Greek artistic gymnastic championships were observed weekly for the 1999-2000 season. Results: Ninety three (61.6%) acute injuries and 58 (38.4%) overuse syndromes were recorded. The most common anatomical location was the ankle (69 cases, 45.7%), followed by the knee (40 cases, 26.5%). The rate of mild injuries was 26.6% (25 cases), that of moderate injuries was 44% (41 cases), and that of major injuries was 29% (27 cases). The incidence of injury to the ankle and knee was significantly higher in the floor exercise, especially during the landing phase, than in the other events. Conclusions: By its nature, gymnastics predisposes to acute injuries, but up to 75% are mild or moderate. Special attention should be paid to the floor exercise, especially the landing phase.